Dilemmas of agro-environmental management for the 2014-2020 programming period - Hoyk Edit (Review on agriculture and rural development, 2014)
The environmental impact of agriculture is in the focus of public and scientific interest since the 1980’s. After the economic transition, because of market loss and other reasons, Hungary was characterised by reduced negative environmental effects of agriculture. However, an OECD analysis prognosticated an again growing environmental impact of agriculture in Hungary. The connections between environment and agriculture form an important part of Hungarian Rural Development Programme for the 2014-2020 programming period. The aim of this paper is to provide an analysis of the selected indices of the Hungarian agricultural sector to decide whether to prognosis of the OECD was correct. In accordance with these results, the authors also examine to what degree the Rural Development Program in preparation can contribute to the goals of agro-environmental management, sustainable agriculture and environment protection.